Genomic Analyses of Halioticoli Clade Species in Vibrionaceae Reveal Genome Expansion With More Carbohydrate Metabolism Genes During Symbiotic to Planktonic Lifestyle Transition - Jiang, Chunqi; Mino, Sayaka; Sawabe, Tomoo (Frontiers in Marine Science, 2022)
Vibrionaceae is one of the most diverse bacterial families and is currently classified into over 50 clades, some members of which play an important role in the symbiotic relationships with humans and animals. Halioticoli clade, which currently consists of 10 species: 8 species associated with the gut of abalone (symbiotic), 1 species (V. breoganii) from bivalves, and 1 species (V. ishigakensis) from subtropical seawater (planktonic). To accelerate studies in the evolution, ecogenomics, and biotechnology of Halioticoli clade species, the genomic backbones and pangenome analyses based on complete genome sequences are needed. Genome sizes of Halioticoli clade species ranged from 3.5 Mb to 4.8 Mb, with V. ishigakensis the biggest. The evolutionary relationships using multilocus sequence analysis based on eight housekeeping genes and 125 single-copy core genes revealed a division of five sub-clades in this clade; 1) V. breoganii, V. comitans, V. inusitatus and V. superstes, 2) V. ezurae, V. neonatus, and V. halioticoli, 3) V. rarus, 4) V. gallicus, and 5) V. ishigakensis. The pan-genomic analysis combined with function and metabolism estimations showed that the planktonic group (sub-clade 5) contained the greatest number of specific genes, and more genes responsible for carbohydrate metabolisms, especially the genes encoding D-galactonate degradation. These results demonstrated that the genome expanded by acquiring more abilities for utilizing various carbohydrates during the evolution from symbiotic to a planktonic lifestyle. Moreover, according to Carbohydrate-Active enZYmes (CAZy) profiling, genes encoding alginate degrading enzymes (aly), classified into PL6, PL7, PL15, and PL17 were common in the ten genomes, but sub-clade 1 had the most. Meanwhile, sub-clade 1and 5 also possessed abundant genes related to macroalgae substrates degradation (GHs), which are also responsible for the genome expansion of sub-clade 1 and 5.